ANALYZING THE FINANCIAL PERFORMANCE ASPECT OF THE ACQUISITION OF BANK VICTORIA SYARIAH BY BTN SYARIAH - Nurzianti, Rahma (J-ISCAN: Journal of Islamic Accounting Research, 2025)
This study aims to analyze the acquisition of Bank Victoria Syariah by BTN Syariah in terms of the financial performance of the two institutions, focusing on four main indicators: Return on Assets (ROA), Non-Performing Financing (NPF), Financing to Deposit Ratio (FDR), and Operating Costs to Operating Income (BOPO). The data used are quarterly financial statements for the period March 2023 to December 2024. The results of the analysis show that BTN Syariah has experienced a significant improvement in financial performance, marked by an increase in ROA, a decrease in BOPO, and the stability of FDR and NPF within healthy limits. In contrast, Bank Victoria Syariah experienced fluctuations that reflected a decline in financing efficiency and quality, especially in the run-up to acquisitions, as seen from the increase in BOPO and NPF and the decrease in ROA. These findings show that the acquisition has a positive impact on BTN Syariah, but requires a more effective integration strategy so that financial synergy can be achieved optimally.